Presencia de Dictyocaulus viviparus en bovinos de las sabanas de Arauca, Colombia - Romero-Hurtado, Clara Stefany (2022)
The present study was carried out in the rural area of the department of Arauca, in the Orinoquía region, Colombia. A total of 1351 faecal samples from dual purpose cattle were collected and processed using the Baerman coprological technique for the detection of Dictyocaulus viviparus. A prevalence of 1.7% of D. vivarus is reported in Arauca, whose environmental conditions are considered adverse for the development of the nematode and do not coincide with those traditionally reported in the country and in the world.